Nigeria : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Nigeria. (IMF Staff Country Reports; Country Report ;, 2019)
This Article IV Consultation highlights that Nigeria's economy is still recovering from the substantial terms-of-trade shock that triggered the 2016 recession. Persistent structural and policy challenges constrain growth to below the level needed to reduce vulnerabilities and improve development outcomes. With elections now complete, there is a greater chance for faster policy implementation. The authorities' Economic Recovery and Growth Plan priorities remain appropriate and should be urgently implemented. Revenue-based fiscal consolidation would be required to create space for higher capital and priority spending while improving spending efficiency and strengthening governance. A comprehensive package of urgent policy reforms is required to address vulnerabilities and raise growth over the medium term. The IMF staff suggested that strengthening banking sector resilience requires increasing capital buffers. This includes extending the no dividend distribution rule to all banks with high restructured loans.